1999
DOI: 10.1177/014572179902500608
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Educators' Perspectives on Barriers for Patients and Educators in Diabetes Education

Abstract: Educators appeared to relate many patient barriers to a lack of patient understanding of the evolving nature of diabetes and the subsequent need for educational support. The role of continuing education for all patients needs to be emphasized to the patient during the initial education, as well as to the healthcare community and the patient's support network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 10 publications
2
39
0
3
Order By: Relevance
“…45,46 In this study, the main barriers across most self-care behaviors were cost and depression. These 2 variables were highly correlated with each other.…”
Section: Discussionmentioning
confidence: 80%
“…45,46 In this study, the main barriers across most self-care behaviors were cost and depression. These 2 variables were highly correlated with each other.…”
Section: Discussionmentioning
confidence: 80%
“…5 Factors preventing access to diabetes education are multifaceted and include travel to attend DSME, limited insurance reimbursement for DSME, difficulty attending classes due to work schedule or child care issues, or disabilities that make travel to DSME services challenging. 5,6 The increasing prevalence of diabetes is resulting in limited availability and access to diabetes care services, including access to certified diabetes educators. It is estimated that there is about one certified diabetes educator per 1,400 patients with diabetes in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to self-management expressed by patients with diabetes are strongly associated with adherence to treatment regimens Glasgow, 1994;Polly, 1992;Wilson et al, 1986) and patients' subjective estimates of diabetes control (Lewis, Jennings, Ward, & Bradley,1990). Barriers to physical activity and diet occur most often , the regimen areas most closely associated with lifestyle changes (Rubin, Peyrot, & Saudek, 1991;Sprague et al, 1999). Although assessing patient barriers to learning is a standard of practice for diabetes educators (American Association of Diabetes Educators, 1992), no research was found that compares and contrasts patients' perceptions about diet and exercise barriers with diabetes educators' perceptions of those barriers.…”
mentioning
confidence: 99%